Serum ceramide levels are altered in multiple sclerosis. (September 2021) - Filippatou, Angeliki G; Moniruzzaman, Mohammed; Sotirchos, Elias S; Fitzgerald, Kathryn C; Kalaitzidis, Grigorios; Lambe, Jeffrey; Vasileiou, Eleni; Saidha, Shiv; Prince, Jerry L; Haughey, Norman; Calabresi, Peter A; Bhargava, Pavan
Background: Sphingolipids are myelin components and inflammatory signaling intermediates. Sphingolipid metabolism may be altered in people with multiple sclerosis (PwMS), but existing studies are limited by small sample sizes. Objectives: To compare the levels of serum ceramides between PwMS and healthy controls (HCs) and to determine whether ceramide levels correlate with disability status, as well as optical coherence tomography (OCT)-derived rates of retinal layer atrophy. Methods: We performed targeted lipidomics analyses for 45 ceramides in PwMS ( n = 251) and HCs ( n = 68). For a subset of PwMS, baseline and 5-year Expanded Disability Status Scale (EDSS) assessments ( n = 185), or baseline and serial spectral-domain OCT ( n = 180) were assessed. Results: Several ceramides, including hexosylceramides, lactosylceramides, and dihydroceramides, were altered in PwMS compared with HCs. Higher levels of Cer16:0 were associated with higher odds of EDSS worsening at 5 years in univariable (odds ratio (OR) = 3.84, 95% confidence interval (CI) = 1.41–10.43) and multivariable analyses accounting for age, sex, and race (OR = 2.97, 95% CI = 1.03–8.59). Each 1 ng/mL higher concentration of Hex-Cer22:0 and DH-HexCer22:0 was associated with accelerated rates (μm/year) of ganglion cell + inner plexiform layer (–0.138 ± 0.053, p = 0.01; –0.158 ± 0.053, p = 0.003, respectively) and peripapillary retinal nerve fiber layer thinning (–0.305 ± 0.107, p = 0.004; –0.358 ± 0.106, p = 0.001, respectively). Conclusion: Ceramide levels are altered in PwMS and may be associated with retinal neurodegeneration and physical disability.